Analysis of Vocabulary Forms and Types in the Guyang Cekathak Tradition for Teaching Indonesian to Foreign Speakers (BIPA): Analisis Bentuk dan Jenis Kosakata dalam Tradisi Guyang Cekathak untuk Pembelajaran BIPA - Vita Verliana; Sri Surachmi; Luthfa Nugraheni (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
This study aims to describe the forms and types of vocabulary in the Guyang Cekathak tradition and its relevance in teaching Indonesian to foreign speakers (BIPA). This study uses a qualitative approach with a descriptive ethnographic method. The research was conducted in Colo Village, Dawe District, Kudus Regency, Central Java, with three informants consisting of religious leaders, village officials, and caretakers. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted through data reduction, vocabulary classification based on morphological form, data presentation, and conclusion drawing. The results showed that the vocabulary forms in this tradition included basic vocabulary, affixed vocabulary, compound words, and repeated words, with a predominance of basic vocabulary. Based on their function, the vocabulary was classified into six types, namely religious, social, objects, rituals and processions, sacred figures and places, and conceptual or descriptive. The vocabulary in the Guyang Cekathak tradition has the potential to be used as teaching material for Indonesian as a foreign language based on local culture because it helps foreign learners understand the Indonesian language as well as the culture of the local community.